PERAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN LEMBAGA KEUANGAN SYARIAH : STUDI ANALISIS HUKUM - Erwin Azhari (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
This research explores the role of the Financial Services Authority (OJK) in supervising Islamic financial institutions in Indonesia through the lens of legal analysis. The main objectives of this research are to analyze the legal framework governing the authority of the OJK, identify the supervisory mechanisms applied, and assess the effectiveness of supervision of Islamic financial institutions. The method used in this research is qualitative with a normative juridical approach, using primary legal materials in the form of laws and regulations, as well as secondary legal materials derived from literature related to Islamic finance law. The results showed that OJK has strong authority in supervising Islamic financial institutions in accordance with Law No. 21 of 2011. The supervisory system applied uses a risk-based approach combined with sharia principles. However, there are several challenges in its implementation, such as the complexity of Islamic financial products and the need for regulatory harmonization. This study recommends improving coordination between OJK and the National Sharia Council-MUI, developing more adaptive supervisory technology, and increasing supervisors' competence in sharia aspects to strengthen the effectiveness of supervision of Islamic financial institutions..